Preparation method of perovskite solar cell with acid-modified SnO2 transmission layer
By adjusting the pH value of SnO2 rubber particles by acid, it optimizes its performance in perovskite solar cells, and solves the lack of energy level matching, limited conductivity, and many surface defects in traditional SnO2 rubber particles in perovskite solar cells. The problem of uneven particles has significantly improved the photoelectric conversion efficiency and stability of the device.
Patent Information
- Application Number
- CN202411705188.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Traditional SnO2 rubber particles have problems such as insufficient energy level matching, limited conductivity, many surface defects and uneven particle size in perovskite solar cells, which limit the improvement of device performance and industrial application.
The pH value of SnO2 particles is adjusted by acid, and its particle size, dispersion and surface chemical properties are optimized, so as to enhance its interface matching with the perovskite absorption layer.
It significantly improves the energy level structure, conductivity, crystallinity and surface quality of the electron transport layer, improves the photoelectric conversion efficiency and stability of perovskite solar cells, and meets the industrial production needs of large-area and flexible batteries.
Smart Images

Figure CN119497495A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of perovskite solar cell materials, and specifically to a method for preparing an acid-modified SnO2 transport layer perovskite solar cell. Background Art
[0002] Perovskite solar cells have attracted widespread attention in the photovoltaic field in recent years due to their advantages such as high photoelectric conversion efficiency, low cost and solubility. Among them, the electron transport layer (ETL), as one of the key components of perovskite solar cells, has an important influence on the performance and stability of the device. Tin dioxide (SnO2) has been widely used in the electron transport layer of perovskite solar cells due to its wide band gap, excellent electron transport ability and optical transparency.
[0003] However, SnO2 colloids prepared by traditional methods face many challenges in application, especially in terms of energy level matching, conductivity, surface defects and particle uniformity, which limit the further improvement of device performance. In recent years, researchers have adopted a variety of improvement methods to improve the performance of SnO2 electron transport layer, including metal ion doping, surface modification and nanostructure regulation. For example, metal doping can effectively improve the electron transport performance of SnO2, thereby improving the efficiency of solar cells; surface modification significantly enhances the stability of the device by reducing the interface defect density. However, despite these improvements, traditional SnO2 colloids still have many problems in actual industrial applications. First, insufficient energy level matching makes the electron transfer efficiency between SnO2 and the perovskite layer low, which in turn affects the photoelectric conversion efficiency of the battery. Secondly, the limited conductivity makes the SnO2 colloids unable to effectively transfer electrons, increasing the internal resistance of the device. Surface defects are also an important problem. These defects are prone to interface recombination, further reducing the photoelectric performance. In addition, during the large-area coating process, SnO2 particles tend to aggregate, resulting in uneven film, which in turn affects the overall stability and performance of the battery.
[0004] Therefore, a simple and effective way is urgently needed to improve the performance of SnO2 colloids to meet the needs of industrial production of large-area and flexible perovskite solar cells. Summary of the invention
[0005] In order to solve the defects in the prior art, the present invention provides a method for preparing an acid-modified SnO2 transport layer perovskite solar cell. The present invention uses acid to adjust the pH value of SnO2 colloid particles to prepare an electron transport layer material, which can improve the energy level matching, conductivity and surface quality of the electron transport layer, thereby improving the photoelectric conversion efficiency and stability of the perovskite solar cell, and meeting the industrial production needs of large-area and flexible batteries.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing an acid-modified SnO2 transport layer material, comprising:
[0008] Sn(OH)4 is subjected to hydrothermal treatment, washing, drying and calcination in sequence to obtain SnO2 nanoparticles;
[0009] The SnO2 nanoparticles are dispersed in a dispersant, and the pH of the system is adjusted to 2-8 with an acid to obtain the product.
[0010] Preferably, the Sn(OH)4 is obtained by reacting a tetravalent tin salt hydrate with a base. In some embodiments of the present invention, it can be obtained by reacting SnCl4·5H2O with a base, or by reacting SnCl2·2H2O with a base after oxidation.
[0011] Preferably, the hydrothermal treatment is carried out at 150-180° C. for 4-6 hours.
[0012] Preferably, the washing is to neutrality.
[0013] Preferably, the calcination condition is 400-500° C. for 1-2 hours.
[0014] Preferably, the SnO2 nanoparticles are dispersed in a dispersant to prepare a 3-5 wt% SnO2 colloidal solution.
[0015] Preferably, the acid is selected from any one or more of hydrochloric acid, nitric acid, acetic acid, oxalic acid, phosphoric acid, sulfuric acid, citric acid, hydrofluoric acid, and polyacrylic acid. The particle size, dispersibility, and surface chemical properties of the SnO2 colloidal particles are precisely controlled, and the SnO2 colloidal particles are optimized according to the acid strength, chelation, and coordination characteristics of the acid to enhance the interface matching between the SnO2 colloidal particles and the perovskite absorption layer.
[0016] In some embodiments of the present invention, the pH of the system is adjusted with acid to any one of 2, 6, 7, 7.2, 7.3, 7.5, 8 or a value between two of them.
[0017] In a second aspect, the present invention provides an acid-modified SnO2 transport layer material prepared by the preparation method.
[0018] In a third aspect, the present invention provides a perovskite solar cell, whose structure includes a transparent conductive substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer, and a metal electrode layer, wherein the electron transport layer is prepared from the acid-modified SnO2 transport layer material.
[0019] The structure of the perovskite solar cell of the present invention includes but is not limited to a planar heterojunction, a mesoporous structure, and an inverted structure.
[0020] In a fourth aspect, the present invention provides a method for preparing a perovskite solar cell, comprising the following steps:
[0021] S1. Clean the transparent conductive substrate;
[0022] S2. Preparation of electron transport layer: depositing the acid-modified SnO2 transport layer material on the transparent conductive substrate;
[0023] S3, preparing a perovskite light absorbing layer on the electron transport layer;
[0024] S4, preparing a hole transport layer on the perovskite light absorbing layer;
[0025] S5. Preparing a metal electrode layer on the hole transport layer.
[0026] Preferably, the transparent conductive substrate material is selected from any one of FTO (fluorine-doped tin oxide), ITO (indium tin oxide), flexible ITO / PEN (polyethylene terephthalate), AZO (aluminum-doped zinc oxide), and GZO (gallium-doped zinc oxide).
[0027] Preferably, in S2, the acid-modified SnO2 transport layer material is deposited on the transparent conductive substrate by any method such as spin coating, dip coating, spray coating or scraping coating.
[0028] Preferably, the deposition process in S2 needs to be annealed at 100-180° C. for 30-60 minutes, and the thickness of the resulting electron transport layer is 30-50 nm. The specific thickness can be adjusted according to device requirements.
[0029] Preferably, the material of the perovskite light absorbing layer is selected from MAPbI x Br y Cl 3-x-y , FAPbI x Br y Cl 3-x-y , CsPbI x BryCl 3-x-y 、CszFA1-zPbI x Br y Cl 3-x-y , Cs z FA k MA 1-z-k PbI x Br y Cl 3-x-y 、(FAPbI3) x (MAPbBr3) 1-xOne or more of the following; wherein, x=0~3, y=0~3, z=0~3, k=0~3.
[0030] Preferably, S3 specifically comprises: depositing the perovskite precursor solution on the electron transport layer. The present invention can adopt a one-step method, a two-step method or a multi-step deposition method, and deposit it on the electron transport layer by any method such as spin coating, dip coating, spray coating, scraping, evaporation, atomic deposition, etc., and annealing treatment to form a well-crystallized perovskite absorption layer with a thickness of 50nm to 1μm. The specific thickness is adjusted according to the light absorption requirements and device design.
[0031] Preferably, the hole transport layer material is selected from any one or more of organic materials, inorganic materials, and carbon materials, and has a thickness of 10 nm to 500 nm to optimize hole transport and interface matching.
[0032] Preferably, the organic material is selected from any one or more of Spiro-OMeTAD, PTAA, and P3HT.
[0033] Preferably, the inorganic material is selected from any one or more of NiOx, CuSCN, and CuI.
[0034] Preferably, the carbon material is graphene and / or carbon nanotubes.
[0035] Preferably, the metal electrode layer is deposited by thermal evaporation, electron beam evaporation, sputtering, printing and the like, and the material may be any one of gold, silver, copper, aluminum, nickel, carbon-based and alloys thereof or composite materials to meet the comprehensive requirements of conductivity, stability and cost.
[0036] The beneficial effects of the present invention are:
[0037] The core of the present invention in the process of preparing the acid-modified SnO2 transport layer material is to accurately control the pH value of the SnO2 colloidal solution through acid regulation to control the particle size, dispersibility and surface chemical properties of the SnO2 colloidal particles, and optimize the SnO2 colloidal particles according to the acid strength, chelation and coordination characteristics of the acid to enhance the interface matching between the SnO2 colloidal particles and the perovskite absorption layer. The method of the present invention is simple and easy to operate, has strong controllability, is applicable to the regulation strategy of various acids, can select the appropriate acid type and concentration according to actual needs, and has high adjustability and adaptability. The method does not require complex equipment and high temperature and high pressure conditions, is easy to realize industrial production, and has good repeatability and scalability.
[0038] The present invention improves the energy level structure, conductivity, crystallinity and surface quality of the electron transport layer when preparing perovskite solar cells by precisely controlling the pH value of the SnO2 colloidal solution, reduces interface states and surface defects, reduces non-radiative recombination losses, achieves optimal energy level matching with the perovskite active layer, and promotes efficient separation and transmission of electrons. Thus, the open circuit voltage, short circuit current and fill factor of the device are significantly improved. In addition, the optimized SnO2 colloidal solution has good dispersibility and stability, can be uniformly formed on a large area and flexible substrate, the film surface is flat and smooth, and the thickness is uniform, providing reliable guarantee for large-scale coating process.
[0039] The preparation method and device structure of the present invention are applicable to various types of perovskite solar cells, including planar heterojunction, mesoporous structure, inverted structure, etc., and have broad application prospects. By adding an encapsulation layer or an interface modification layer, the environmental stability of the device is further improved, the service life is extended, and the requirements of practical applications are met. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Device structure diagram of perovskite solar cell.
[0041] Figure 2 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 1.
[0042] Figure 3 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 2.
[0043] Figure 4 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 3.
[0044] Figure 5 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 4.
[0045] Figure 6 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 5.
[0046] Figure 7 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 6.
[0047] Figure 8 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 7.
[0048] Fig. 9 This is a current density-voltage curve diagram of the perovskite solar cell prepared in Example 8.
[0049] Fig.10This is a light maximum power tracking test diagram of the battery device of Example 4.
[0050] Fig.11 This is the X-ray photoelectron spectroscopy (XPS) graph of the SnO2 thin film of Example 4.
[0051] Fig.12 This is the ultraviolet photoelectron spectroscopy (UPS) diagram of the SnO2 film of Example 4.
[0052] Fig.13 This is an atomic force microscope (AFM) image of the SnO2 thin film of Example 4.
[0053] Fig.14 This is the conductivity diagram of the SnO2 thin film of Example 4. DETAILED DESCRIPTION
[0054] In order to enable those skilled in the art to better understand the technical solution of the invention, the present invention is further described in detail below in conjunction with specific implementation methods.
[0055] Example 1
[0056] This embodiment provides a method for preparing an acid-modified SnO2 transport layer material:
[0057] Dissolve 1.0 g of SnCl4·5H2O in 50 ml of deionized water, slowly add 25%-28% ammonia solution until the pH value rises to 7, and generate white Sn(OH)4 precipitate. Transfer the precipitate to a 100 ml autoclave and hydrothermally treat it at 150°C for 4 hours to generate SnO2 nanoparticles. Wash the SnO2 nanoparticles with deionized water until neutral, dry at 60°C, and calcine at 400°C for 2 hours to obtain SnO2 nanoparticle powder with high crystallinity. Then, prepare an acid-regulated SnO2 colloidal solution, disperse 0.3 g of the calcined SnO2 nanoparticle powder in 10 ml of deionized water, ultrasonically disperse for 30 minutes, add 0.1 ml of 1M acetic acid solution to the solution under stirring, slowly add and continue stirring, and adjust the pH value of the solution to 7.5. Finally, the solution was filtered through a 0.22 μm polytetrafluoroethylene (PTFE) filter membrane to remove possible aggregates and impurities to obtain a uniform SnO2 colloidal solution.
[0058] This embodiment also provides a method for preparing a perovskite solar cell using the acid-modified SnO2 transport layer material, the steps of which are as follows:
[0059] S1. Clean the transparent conductive substrate: Take an ITO conductive glass substrate with a size of 2.5cm×2.5cm and perform ultrasonic cleaning. Place the substrate in deionized water containing about 2% detergent for ultrasonic cleaning for 15 minutes to remove oil and particulate matter on the surface; then rinse the substrate thoroughly with deionized water to ensure that there is no residual detergent; then place the substrate in anhydrous ethanol and anhydrous isopropanol in turn, and perform ultrasonic cleaning in each solvent for 10 minutes to remove organic contamination; after cleaning, blow dry the surface of the substrate with high-purity nitrogen, and perform ultraviolet ozone treatment for 15 minutes to increase the surface hydrophilicity and promote the uniform deposition of subsequent thin films.
[0060] S2. Preparation of electron transport layer: Add the SnO2 colloidal solution prepared above to the cleaned ITO substrate and spin coat it at 3000 rpm for 30 seconds to ensure the uniformity and density of the film; pre-bake the spin-coated substrate at 100°C for 10 minutes, and then anneal at 150°C for 60 minutes to form a SnO2 electron transport layer with a thickness of about 50 nm.
[0061] S3. Preparation of perovskite light-absorbing layer: 1.8 mmol of PbI2 (0.8298 g) and 1.8 mmol of CH3NH3I (0.2861 g) were dissolved in 1 ml of a mixed solvent of DMF and DMSO (volume ratio of 8:1), and stirred at 60°C for 1 hour to obtain a clear perovskite precursor solution; the solution was filtered through a 0.45 μm filter membrane and deposited on the electron transport layer by a two-step spin coating method, the first step was spin coating at 1000 rpm for 10 seconds, and the second step was spin coating at 5000 rpm for 30 seconds. During the process, 200 μL of chlorobenzene was added after 15 seconds of spin coating to promote the rapid nucleation and growth of perovskite crystals; after spin coating, the substrate was annealed on a 100°C hot plate for 10 minutes to form a MAPbI3 perovskite light-absorbing layer with a thickness of about 500 nm.
[0062] S4. Preparation of hole transport layer: 72.3 mg of Spiro-OMeTAD was dissolved in 1 ml of chlorobenzene, 28.8 μL of tBP (4-tert-butylpyridine) and 17.5 μL of Li-TFSI (lithium bis(trifluoromethanesulfonyl imide)) solution were added, and after stirring at room temperature for 30 minutes, the solution was dropped on the perovskite light-absorbing layer and spin-coated at 3000 rpm for 30 seconds to form a hole transport layer with a thickness of about 150 nm; then, the device was placed in an environment with a relative humidity of about 20% and allowed to stand for 12 hours to allow the Spiro-OMeTAD to undergo oxidative doping.
[0063] S5. Preparation of metal electrodes: Fix the oxidized sample on the sample stage of the vacuum evaporation equipment and reduce the vacuum degree to better than 5×10 -4 Pa, a silver electrode with a thickness of 100 nm was evaporated by thermal evaporation process, and the sample was taken out for testing after cooling to room temperature.
[0064] The device structure of the obtained perovskite solar cell is shown in the figure below: Figure 1 shown.
[0065] Example 2
[0066] This embodiment provides a method for preparing an acid-modified SnO2 transport layer material:
[0067] Dissolve 1.0 g SnCl2·2H2O in 50 ml deionized water to form a transparent Sn 2+ Precursor solution. Under stirring, hydrogen peroxide (H2O2, 30%) was added dropwise to the solution until the solution turned transparent and light yellow, indicating that Sn 2+ Oxidized to Sn 4+ . Slowly drop 1M NaOH solution, keep stirring and monitor the pH value. When the pH value reaches 8, a white Sn(OH)4 precipitate is generated. The precipitate is transferred to a 100 ml high-pressure reactor and hydrothermally treated at 180°C for 6 hours to generate SnO2 nanoparticles with higher crystallinity. The SnO2 nanoparticles are washed with deionized water until neutral and dried at 60°C to obtain SnO2 nanoparticle powder. Calcination at 500°C in air for 1 hour improves the crystal quality and conductivity of SnO2. 0.5 g of the calcined SnO2 nanoparticle powder is dispersed in a mixed solvent of 10 ml of deionized water and anhydrous ethanol (volume ratio 1:1) to form a SnO2 colloidal solution with a concentration of 5wt%, which is treated under 40kHz ultrasonic conditions for 60 minutes to ensure that the nanoparticles are fully dispersed to form a stable colloidal solution. Under stirring conditions, 0.2 ml of 0.5 M oxalic acid solution was added to the solution, slowly added dropwise and stirred continuously, and the pH value of the solution was adjusted to 7.2. Finally, the solution was filtered with a 0.45 μm polytetrafluoroethylene filter membrane to remove possible aggregates and impurities to obtain a uniform SnO2 colloidal solution.
[0068] This embodiment also provides a method for preparing a perovskite solar cell using the acid-modified SnO2 transport layer material, the steps of which are as follows:
[0069] S1. Cleaning the transparent conductive substrate: the transparent conductive substrate is a FTO conductive glass substrate, and the cleaning method is the same as that in Example 1.
[0070] S2. Preparation of electron transport layer: The prepared SnO2 colloidal solution was dropped onto the cleaned FTO substrate and spin coated at 4000 rpm for 20 seconds to ensure the uniformity and density of the film; the spin-coated substrate was placed on a hot plate and then annealed in air at 180°C for 60 minutes to form a SnO2 electron transport layer with a thickness of about 40 nm.
[0071] S3. Preparation of perovskite light-absorbing layer: 1.5 mmol of lead iodide (PbI2, 0.693 g), 0.75 mmol of lead bromide (PbBr2, 0.275 g), 1.0 mmol of methylamine iodide (CH3NH3I, 0.159 g) and 0.5 mmol of methylamine bromide (CH3NH3Br, 0.056 g) were dissolved in 1 ml of a mixed solvent (volume ratio of 3:2) of γ-butyrolactone (GBL) and dimethyl sulfoxide (DMSO), and 40 μL of isopropanol solution of methylammonium chloride (MACl, 2 M) was added to improve the growth and stability of perovskite crystals. The mixture was stirred at 70°C for 2 hours until a clear and transparent perovskite precursor solution was formed. The precursor solution was filtered using a 0.22 μm PTFE filter to remove insoluble matter, and the precursor solution was dripped onto the electron transport layer using a two-step spin coating method: the first step was to spin coat at 500 rpm for 5 seconds to ensure uniform spreading of the solution, and the second step was to spin coat at 4000 rpm for 30 seconds to accelerate the evaporation of the solvent and form a uniform precursor film. Ten seconds after the start of the second step of spin coating, 150 μL of ether was quickly dripped onto the center of the rotating substrate to promote the rapid nucleation and growth of perovskite crystals and improve the film quality. After the spin coating was completed, the substrate was annealed on a hot plate at 100 °C for 15 minutes to form a mixed halogen MAPb(I 0.89 Br 0.11 )3Perovskite light absorbing layer.
[0072] S4. Preparation of hole transport layer: Polytrihexylthiophene (P3HT) was used as hole transport material. 10 mg of P3HT was dissolved in 1 ml of chloroform and stirred for 1 hour to form a 1 wt% P3HT solution. The P3HT solution was dripped onto the perovskite layer and spin-coated at 2000 rpm for 60 seconds to form a P3HT hole transport layer with a thickness of about 100 nm. The spin-coated substrate was placed on a hot plate at 80°C for annealing for 10 minutes to improve the crystallinity and conductivity of P3HT.
[0073] S5. Preparation of metal electrode: same as in Example 1.
[0074] Example 3
[0075] This embodiment provides a method for preparing an acid-modified SnO2 transport layer material:
[0076] The same as Example 1, except that when preparing the acid-controlled SnO2 colloidal solution, 0.05 ml of 1M nitric acid (HNO3) solution was added to the solution to adjust the pH value of the solution to 7.3.
[0077] This embodiment also provides a method for preparing a perovskite solar cell from the acid-modified SnO2 transport layer material. The steps are the same as those in Embodiment 1, except that the SnO2 colloidal solution prepared in this embodiment is used in preparing the electron transport layer.
[0078] Example 4
[0079] The preparation method of the acid-modified SnO2 transport layer material is the same as that in Example 3.
[0080] This embodiment also provides a method for preparing a perovskite solar cell using the acid-modified SnO2 transport layer material, the steps of which are as follows:
[0081] S1. Clean the transparent conductive substrate: Take a flexible ITO / PEN (polyethylene terephthalate) substrate with a size of 2.5 cm × 2.5 cm, place the substrate in deionized water containing a neutral detergent (about 2% detergent concentration), and ultrasonically clean it for 10 minutes to remove surface oil and dust; then rinse the substrate thoroughly with deionized water until there is no residual detergent on the surface; then place the substrate in anhydrous ethanol and anhydrous isopropanol in turn, and ultrasonically clean it in each solvent for 10 minutes to remove organic contamination; blow dry the surface of the substrate with high-purity nitrogen to prevent water marks from remaining, and place the substrate in an oxygen plasma cleaner for 15 minutes.
[0082] S2. Preparation of electron transport layer: The prepared SnO2 colloidal solution was dropped onto the cleaned flexible ITO / PEN substrate and spin coated at 3000 rpm for 40 seconds to ensure the uniformity and density of the film; the spin-coated substrate was annealed on a hot plate at 100°C for 30 minutes to form a SnO2 electron transport layer with a thickness of about 30 nm.
[0083] The preparation of the perovskite light absorbing layer, the hole transport layer, and the metal electrode is the same as in Example 1.
[0084] Example 5
[0085] The preparation method of the acid-modified SnO2 transport layer material is the same as that in Example 3.
[0086] This embodiment also provides a method for preparing a perovskite solar cell using the acid-modified SnO2 transport layer material, the steps of which are as follows:
[0087] S1. Clean the transparent conductive substrate: Use a 10cm×10cm FTO (fluorine-doped tin oxide) conductive glass substrate to meet the needs of large-area preparation. Place the substrate in deionized water containing neutral detergent (2% dishwashing liquid) and ultrasonically clean it for 30 minutes to remove surface oil and particulate matter; rinse the substrate thoroughly with deionized water until there is no residual detergent on the surface; place the substrate in anhydrous ethanol and anhydrous acetone in turn, and ultrasonically clean it in each solvent for 15 minutes to remove organic contamination; blow dry the surface of the substrate with high-purity nitrogen to prevent water marks from remaining. Place the substrate in a UV ozone cleaner for 30 minutes to increase the surface hydrophilicity and promote the uniform deposition of subsequent thin films.
[0088] S2. Preparation of electron transport layer: The SnO2 colloidal solution was uniformly coated on a large-area FTO substrate by a doctor blade coating method. The doctor blade gap was set to 100 μm and the coating speed was 5 cm / s to ensure the uniformity and consistency of the film. The coated substrate was placed on a hot plate at 80°C and baked for 20 minutes to remove the solvent residue. The substrate was annealed in air at 150°C for 60 minutes to form a SnO2 electron transport layer with a thickness of about 50 nm.
[0089] S3. Preparation of perovskite light-absorbing layer: The perovskite precursor solution described in Example 1 is coated on the SnO2 electron transport layer by a slot-die coating method. The slot-die gap is set to 50 μm, the coating speed is 10 mm / s, the substrate temperature is controlled at 50°C, and the coated substrate is placed on a hot plate at 100°C for annealing for 30 minutes to form a uniform perovskite light-absorbing layer with a thickness of about 500 nm.
[0090] S4. Preparation of hole transport layer: same as in Example 1.
[0091] S5. Preparation of metal electrode: same as in Example 1.
[0092] Example 6
[0093] This embodiment provides a method for preparing an acid-modified SnO2 transport layer material:
[0094] The same as Example 1, except that when preparing the acid-regulated SnO2 colloidal solution, 0.05 ml of 1M hydrochloric acid (HCl) solution was added to the solution to adjust the pH value of the solution to 2.0.
[0095] This embodiment also provides a method for preparing a perovskite solar cell from the acid-modified SnO2 transport layer material. The steps are the same as those in Embodiment 5, except that the SnO2 colloidal solution prepared in this embodiment is used in preparing the electron transport layer.
[0096] Example 7
[0097] This embodiment provides a method for preparing an acid-modified SnO2 transport layer material:
[0098] The same as Example 1, except that when preparing the acid-controlled SnO2 colloidal solution, 0.05 ml of 1M phosphoric acid (H3PO4) solution was added to the solution to adjust the pH value of the solution to 8.0.
[0099] This embodiment also provides a method for preparing a perovskite solar cell from the acid-modified SnO2 transport layer material. The steps are the same as those in Embodiment 5, except that the SnO2 colloidal solution prepared in this embodiment is used in preparing the electron transport layer.
[0100] Example 8
[0101] This embodiment provides a method for preparing an acid-modified SnO2 transport layer material:
[0102] The same as Example 1, except that: when preparing the acid-controlled SnO2 colloidal solution, 0.05 ml of 1M polyacrylic acid (C5H 10 O2) solution and adjust the pH value of the solution to 7.2.
[0103] This embodiment also provides a method for preparing a perovskite solar cell from the acid-modified SnO2 transport layer material. The steps are the same as those in Embodiment 5, except that the SnO2 colloidal solution prepared in this embodiment is used in preparing the electron transport layer.
[0104] Comparative Example 1
[0105] This comparative example provides a method for preparing an electron transport layer material:
[0106] The same as Example 1, except that there is no step of using acid to regulate the SnO2 colloidal solution.
[0107] This comparative example also provides a method for preparing a perovskite solar cell from the electron transport layer material, and the steps are the same as those in Example 1, except that SnO2 prepared in this comparative example is used in preparing the electron transport layer.
[0108] Effect Example 1 Battery Performance Test
[0109] The solar cells prepared in Examples 1 to 8 were subjected to a cell performance test under the following conditions: an AM1.5G solar simulator with a light intensity of 100 mW / cm 2 The test equipment is Keithley 2400 source meter, and the effective area of the active layer is 0.0625cm 2 .
[0110] The JV curves of Examples 1 to 8 and Comparative Example 1 are shown in Figures 2 to 9 , the data are shown in Table 1.
[0111] Table 1
[0112]
[0113] Depend on Figures 2 to 9 As can be seen from Table 1, compared with Comparative Example 1, the photoelectric performance indicators such as short-circuit current density, open-circuit voltage, fill factor, and photoelectric conversion efficiency of the perovskite solar cell prepared by acid-regulating the pH value of SnO2 in the embodiment of the present invention are significantly improved, indicating that the preparation method of the present invention can effectively improve the battery performance of the perovskite solar cell, among which Example 4 is a preparation method for a flexible battery, and Examples 5 to 8 are preparation methods for large-area batteries, indicating that the method of the present invention can meet the industrial production needs of large-area and flexible batteries.
[0114] Fig.10 The maximum power tracking test diagram of the cell device prepared in Example 4 shows that the maximum power tracking of the perovskite solar cell prepared by the acid-regulated SnO2 colloidal solution of the present invention can still maintain 94.5% of the initial efficiency after 1200 hours, reflecting the stability of the solar cell of the present invention. However, the efficiency and stability of the solar cell prepared in Comparative Example 1 under the same conditions are significantly reduced.
[0115] Effect Example 2 Performance Test of SnO2 Thin Film
[0116] Fig.11 It is an X-ray photoelectron spectrum (XPS) diagram of the electron transport layer (SnO2 film) prepared in Example 4, which shows the X-ray photoelectron spectrum (XPS) spectra of the SnO2 nanoparticle powder (upper figure) without acid regulation of Comparative Example 1 and the SnO2 sample (lower figure) treated with acid regulation in Example 4. By comparing the spectra of the two, the chemical changes caused by acid regulation can be analyzed. The main peak of O1s in the XPS spectrum can be deconvoluted into multiple sub-peaks, which correspond to oxygen in different chemical states in the material. By comparing the binding energy positions of the upper figure (SnO2) and the lower figure (SnO2+HNO3), the displacement of the binding energy and the change in the intensity of the peak can be found, which indicates that after HNO3 treatment, the chemical environment of oxygen has changed. In the SnO2 without acid regulation, the main peak is located near about 530eV, which is usually attributed to lattice oxygen (O 2- ); after HNO3 treatment, new sub-peaks or increased intensities may appear in the binding energy region of 531-533 eV, which may represent additional oxygen-containing groups such as surface hydroxyl groups or adsorbed water. The relative contents of different oxygen species can be estimated by quantitative analysis of the sub-peak areas, and the effect of HNO3 treatment on the chemical environment of the SnO2 surface can be quantified.
[0117] Fig.12 This is the ultraviolet photoelectron spectrum (UPS) diagram of the electron transport layer (SnO2 film) prepared in Example 4. It can be seen that, compared with Comparative Example 1, the work function of the SnO2 film prepared from the SnO2 colloidal solution after acid-controlled pH is significantly reduced, which is beneficial to energy level matching.
[0118] Fig.13 This is an atomic force microscope (AFM) image of the electron transport layer (SnO2 film) prepared in Example 4. It can be seen that compared with Comparative Example 1, the roughness of the electron transport layer film obtained in Example is significantly reduced, which is more conducive to the growth of perovskite crystals.
[0119] Fig.14 This is the conductivity diagram of the electron transport layer (SnO2 film) prepared in Example 4. It can be seen that, compared with Comparative Example 1, the conductivity of the SnO2 film prepared from the SnO2 colloidal solution after acid-controlled pH is significantly improved, which is beneficial to the transport of carriers.
[0120] The above characterization results indicate that the method of the present invention can optimize the physicochemical properties of the SnO2 electron transport layer, improve its energy level matching, conductivity, crystallinity and surface quality, thereby improving the photoelectric conversion efficiency and stability of perovskite solar cells and meeting the needs of industrial production of large-area and flexible batteries.
[0121] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing an acid-modified SnO2 transport layer material, characterized in that: include: Sn(OH)4 is subjected to hydrothermal treatment, washing, drying and calcination in sequence to obtain SnO2 nanoparticles; The SnO2 nanoparticles are dispersed in a dispersant, and the pH of the system is adjusted to 2-8 with an acid to obtain the product.
2. The preparation method according to claim 1, characterized in that: The SnO2 nanoparticles are dispersed in a dispersant to prepare a 3-5wt% SnO2 colloidal solution.
3. The preparation method according to claim 1 or 2, characterized in that: The acid is selected from any one or more of hydrochloric acid, nitric acid, acetic acid, oxalic acid, phosphoric acid, sulfuric acid, citric acid, hydrofluoric acid, and polyacrylic acid.
4. An acid-modified SnO2 transport layer material prepared by the preparation method according to any one of claims 1 to 3.
5. A perovskite solar cell, characterized in that: Its structure includes a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer, and a metal electrode layer, wherein the electron transport layer is prepared from the acid-modified SnO2 transport layer material described in claim 4.
6. A method for preparing a perovskite solar cell, characterized in that: The following steps are involved: S1. Clean the transparent conductive substrate; S2. Preparation of electron transport layer: depositing the acid-modified SnO2 transport layer material according to claim 4 on the transparent conductive substrate; S3, preparing a perovskite light absorbing layer on the electron transport layer; S4, preparing a hole transport layer on the perovskite light absorbing layer; S5. Preparing a metal electrode layer on the hole transport layer.
7. The preparation method according to claim 6, characterized in that: The transparent conductive substrate material is selected from any one of FTO, ITO, flexible ITO / PEN, AZO and GZO.
8. The preparation method according to claim 6, characterized in that: The material of the perovskite light absorbing layer is selected from MAPbI x Br y Cl 3-x-y , FAPbI x Br y Cl 3-x-y , CsPbI x BryCl 3-x-y 、CszFA1-zPbI x Br y Cl 3-x-y , Cs z FA k MA 1-z- k PbI x Br y Cl 3-x-y 、(FAPbI3) x (MAPbBr3) 1-x One or more of the following; wherein, x=0~3, y=0~3, z=0~3, k=0~3.
9. The preparation method according to claim 6, characterized in that: The hole transport layer material is selected from any one or more of organic materials, inorganic materials and carbon materials.
10. The preparation method according to claim 6, characterized in that: The metal electrode layer material is selected from any one of gold, silver, copper, aluminum, nickel, carbon-based materials, and alloys or composite materials thereof.
Citation Information
Patent Citations
Preparation method of tin dioxide microspheres
CN106542571A
Tin-based perovskite solar cell with a hole transport layer and preparation method thereof
CN112186107A
Preparation method of tin oxide electron transport layer and perovskite solar cell
CN114242906A
Perovskite battery based on acid-treated tin oxide and preparation thereof
CN114551723A
Perovskite solar cell preparation method and perovskite solar cell
CN117998940A